Effect of high-speed running on hamstring strain injury risk. Issue 24 (10th June 2016) - Duhig, Steven; Shield, Anthony J; Opar, David; Gabbett, Tim J; Ferguson, Cameron; Williams, Morgan
Abstract : Background: Hamstring strain injuries (HSIs) are common within the Australian Football League (AFL) with most occurring during high-speed running (HSR). Therefore, this study investigated possible relationships between mean session running distances, session ratings of perceived exertion (s-RPE) and HSIs within AFL footballers. Methods: Global positioning system (GPS)-derived running distances and s-RPE for all matches and training sessions over two AFL seasons were obtained from one AFL team. All HSIs were documented and each player's running distances and s-RPE were standardised to their 2-yearly session average, then compared between injured and uninjured players in the 4 weeks (weeks −1, −2, −3 and −4) preceding each injury. Results: Higher than 'typical' (ie, z=0) HSR session means were associated with a greater likelihood of HSI (week −1: OR=6.44, 95% CI=2.99 to 14.41, p<0.001; summed weeks −1 and −2: OR=3.06, 95% CI=2.03 to 4.75, p<0.001; summed weeks −1, −2 and −3: OR=2.22, 95% CI=1.66 to 3.04, p<0.001; and summed weeks −1, −2, −3 and −4: OR=1.96, 95% CI=1.54 to 2.51, p<0.001). However, trivial differences were observed between injured and uninjured groups for standardised s-RPE, total distance travelled and distances covered whilst accelerating and decelerating. Increasing AFL experience was associated with a decreased HSI risk (OR=0.77, 95% CI 0.57 to 0.97, p=0.02). Furthermore, HSR data modelling indicated that reducing mean distances in week −1 may decrease the probability of HSI. Conclusions: Exposing players to large and rapid increases in HSR distances above their 2-yearly session average increased the odds of HSI. However, reducing HSR in week −1 may offset HSI risk.